2005
DOI: 10.1111/j.1572-0241.2005.41857.x
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Glucuronosyltransferase 1A7 Genetic Polymorphisms Are Associated with Hepatocellular Carcinoma Risk and Onset Age

Abstract: An inverse dose-response relationship was demonstrated between the detoxifying activity of the UGT1A7 genotypes and HCC. Of the male HCC patients, median onset age for those carrying an UGT1A7 low-activity genotype was 9 yr lower than those bearing the high-activity variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 28 publications
1
32
1
Order By: Relevance
“…Again, low-activity UGT1A7 variants were found to be associated with incidence of HCC in this population. A larger study including 217 HCC patients and 291 controls corroborated these findings when it was reported that the low-activity UGT1A7 polymorphisms correlated with HCC risk (OR 3.06; 95% CI 1.50-6.24) (Tseng et al, 2005). Additionally, in male patients, the age of onset was earlier in the low-activity UGT1A7 genotypes, as against males with the wild-type allele (median age 50 versus 59 years, Po0.05).…”
Section: Hepatocellular Carcinomasupporting
confidence: 71%
“…Again, low-activity UGT1A7 variants were found to be associated with incidence of HCC in this population. A larger study including 217 HCC patients and 291 controls corroborated these findings when it was reported that the low-activity UGT1A7 polymorphisms correlated with HCC risk (OR 3.06; 95% CI 1.50-6.24) (Tseng et al, 2005). Additionally, in male patients, the age of onset was earlier in the low-activity UGT1A7 genotypes, as against males with the wild-type allele (median age 50 versus 59 years, Po0.05).…”
Section: Hepatocellular Carcinomasupporting
confidence: 71%
“…Recently, we reported that genetic polymorphisms in interleukin-1b and UDP glucuronosyltransferase 1A7 genes were associated with the development of hepatocellular carcinoma in Japanese patients with chronic HCV infection (13,14), which was followed by similar reports by other groups as well (16). We further did a large-scale search of gene polymorphisms associated with the hepatocellular carcinoma development in a much larger population of HCV patients and found that three single nucleotide polymorphisms (SNP) in three genes (SCYB14, GFRA1, and CRHR2) were significantly associated with hepatocellular carcinoma development in Japanese patients with chronic HCV infection (15).…”
mentioning
confidence: 49%
“…UGT1A7 gene. There were six eligible studies including 862 cases and 1546 controls explored the associations between the two SNPs and HCC (Vogel et al 2001;Wang et al 2004;Tseng et al 2005;Borentain et al 2007;Stucker et al 2007;Kong et al 2008). We extracted two polymorphisms' genotype data from the articles to do the meta-analyses.…”
Section: Resultsmentioning
confidence: 99%